Utilization Of Privilege Escalation Vulnerability In Manipulating Administrator Access Of PT XYZ - Ritonga, Jody Jeremi Hadrian; Sihotang, Jay Idoan (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
PT.XYZ is a CRM solutions provider that helps businesses manage their interactions with customers. Through in-depth research, a security vulnerability was discovered on PT.XYZ's platform that could be exploited by unauthorized parties to escalate their access rights unlawfully. This research involved a comprehensive analysis of CRM system. The research method included application analysis, exploitation, impact evaluation, solution development, and reporting. The findings revealed a vulnerability in the user management mechanism, allowing a regular user to escalate their access rights to an administrator level. This could potentially lead to customer data misuse, operational disruptions, and financial losses for the company. The research process involved penetration testing, impact analysis, and the development of mitigation solutions. Thanks to these findings, PT.XYZ has implemented system improvements to address the security gap. This research demonstrates the importance of conducting regular security testing to ensure a company's information systems remain protected from cyber threats.